The understanding of dependence structure measurement: Evidence from natural rubber imports of ASEAN - Kewalin Somboon (2020)
© 2019 IOP Publishing Ltd. All rights reserved. This paper is proposed to focuses on the time series data study and rare structures of natural rubber, which cannot precise imply in regular non-linear estimation. The Maximum entropy bootstrapping estimator (MEboot), Stochastic dominance, the AR-GARCH model and Copula models were applied to research the outcome of natural rubber demand in ASEAN. The results illustrate which countries were the dominator who leads rubber importing trend in ASEAN region and also beneficial for develop policies concerned by the natural rubber production development and promotion.